Methodology of the Book of the Holy Qur'an and The Massage of Qur'an: A Comparative Study of the Book of Tafsir by A. Yusuf Ali and Muhammad Asad - Nursidik, Ihsan; Komarudin, Edi (UIN Sunan Gunung Djati Bandung, 2023)
The study of the methodology of interpreting the Qur'an is one of the disciplinary studies in the field of Qur'anic Science and Tafsir. His studies have always been literature that animates the discourse of interpretation. The more mushrooming the development of scientific Tafsir of Tafsir among the public, the more widespread the products of this interpretation are developing. Even not only in the original language—namely Arabic, but the development of the science of interpretation of the Qur'an has met its new reality, where variants of the interpretation of books from various languages have begun to appear. One of them is an English commentary, such as the one initiated by Abdullah Yusuf Ali and Muhammad Asad. This study aims to analyze the methodology of the book of Tafsir The Holy Qur'an by A. Yusuf Ali and The Massage of the Qur'an by Muhammad Asad. This research is a qualitative research with descriptive analysis approach. The results of this study show that the interpretation methods of Ali and Asad have similarities, including in: first, sources based on ra'i; second, methods of interpretation of ijmali and third, display of interpretations using footnotes. The difference between the two lies in the style of interpretation, then the features of the template in the interpretation.